Climate Change, Flood Disaster Assessment and Human Security in Katsina State, Nigeria. (American Journal of Human Ecology, 2015)
This study examines the recent rainfall trends and occurrence of floods in Katsina State. Annual and monthly rainfall data for Katsina from the period 1985 to 2014 were used to analyze the rainfall trends. The standard deviation was then used to determine the rainfall deviation from the normal. The paper focused on the floods event of 2012 and 2013 in the state and the implications for human security. Floods data were obtained from Katsina State Emergency Management Agency, and a total of 200 copies of a questionnaire were administered to flood affected communities in order to obtain information of the causes and damages from the flood hazards of 2012 and 2013. Trend analysis was used to determine the rainfall changes and the results show an increase in rainfall amount in the months of June, July and August which is one of the factors responsible for the frequent occurrences of floods in those months. The major implication of this finding is that infrastructures built on the perceived decreasing rainfall have to be reviewed. The study recommends that, for sustainable development, planning and designing of infrastructures should take into account the recent rainfall trends and occurrences of floods in the area.